E- BOOK Vs AUDIO BOOK E-RESOURCES, A COMPARATIVE STUDY WITH OVERVIEW OF TRADITIONAL RESOURCES - S. M, Mr. Mallikarjun; Patil, Mr. S. G. (IJRDO- Journal of Educational Research, 2018)
The present environment is completely involved with e-resources and online materials. Technology has cope-up the all kind of generations. Users are the ultimate decision makers of this era. The latest technology has offered anything and everything to the users’ hand only in the form of smart phones. There are massive of information made available on the internet and most of them are available as free for end users. Similarly, there is an information/applications over the internet, which can facilitate to read and listen the e-content as well, basis on the user needs. The article tries to through the light over some of the most useful e-reader and audiobook applications which are available as free of cost with lots of user friendly features like, services, compatibilities and interoperability’s etc. A key features over the traditional resources also discussed.